Dynamism in Islamic Activism Reference Points for Democratization and Human Rights - Raad voor het Regeringsbeleid, Wetenschappelijke (Amsterdam University Press, 2006)
The increased tensions surrounding radical Muslims and radical movements in the political Islam are not only manifested in the Western countries but also in the Muslim world itself. Tendencies and political movements that undermine the status quo have proliferated since the 1970s. They plead for a far-reaching islamization: funding politics, law and society on Islamic foundations. This study of the Netherlands Scientific Council for Government Policy (WRR) analyses the developments in Islamic beliefs, political activism, society and law since the 1970s. To what extent has islamization been successful? What are its consequences for attempts in and outside the Muslim world to come to extend democratization and respect for human rights? And what can the Netherlands and the European Union contribute to support developments towards democratization and human rights? This study is, among others, based on "http://www.aup.nl/do.php?a=show_visitor_booklist&b=series&series=33">extensive research of experts on the change of Islamic thinking and to the dynamics of law in twelve different Muslim countries. This title is available in the OAPEN Library - http://www.oapen.org.
English
Keywords: Politics & government; Comparative politics; Sociology; Politics and government; Comparative politics; Sociology; Political Science; Sociology